Seed multiplication and preliminary evaluations of Phaseolus coccineus germplasm collection at C.I.A.T. (Centro Internacional de Agricultura Tropical, Cali, Colombia) - Schmit, Véronique; Baudoin, Jean-Pierre (1986)
Seed increase of the 1300 accessions from both the cultivated subspecies (coccineus and polyanthus) and the wild forms of Phaseolus coccineus is being carried out at 2 locations of Colombia. In Popayan (1700 m alt., 18 degrees Celsius mean temp., and 2000 mm annual rainfall), 12 plants of each accession are grown in mesh cages. Flowers are hand-pollinated with pollen from the same plants or plants from the same population. In total, 70 accessions can be multiplied twice a year at this location. In Rionegro (2200 m alt., 17 degrees Celsius mean temp. and 1850 mm annual rainfall), 18 plants from each accession are grown in the open field. Plant are hand-pollinated in the same way as in Popayan but paper bags are used to protect the hand-pollinated racemes from insect activities. This method allows the seed increase of 350 accessions a year. A preliminary screening of accessions of the subspecies polyanthus has also been carried out to identify sources of resistance to Ascochyta. Four of the accessions tested were particularly outstanding: G 35336 and G 35182 (from Guatemala), G 35337 (from Mexico), and G 35372 (from Colombia). (CIAT)